Taxpayer Compliance in West Kisaran: The Roles of Tax Literacy, Tax Awareness, and Islamic Business Ethics - Lyra Nadia Srg; Nurlaila; Purnama Ramadhani Silalahi (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
Taxes are one of the main sources of government revenue and are essential for financing development and economic growth. However, taxpayer compliance remains a challenge in West Kisaran. This study examines the effects of tax literacy, tax awareness, and Islamic business ethics on taxpayer compliance among individual taxpayers in West Kisaran. A quantitative survey was conducted using questionnaires distributed to 100 individual taxpayers with a Taxpayer Identification Number (NPWP), selected through purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that tax literacy has a positive but statistically insignificant effect on taxpayer compliance. Meanwhile, tax awareness and Islamic business ethics have positive and significant effects on taxpayer compliance. The structural model also indicates strong explanatory power, showing that the three variables account for a substantial portion of the variance in taxpayer compliance. These findings suggest that strengthening taxpayer awareness and Islamic business ethics is more effective than relying solely on tax literacy to improve compliance. This study enriches the literature by highlighting Islamic business ethics as an important determinant of taxpayer compliance in West Kisaran